Development of a Physiologically-Based Pharmacokinetic (PBPK) Model of Nebulized Hydroxychloroquine for Pulmonary Delivery to COVID-19 Patients - Idkaidek, Nasir; Hawari, Feras; Dodin, Yasmeen; Obeidat, Nour (Drug Research, 2020)
Despite inconclusive evidence, chloroquine (CQ) and hydroxychloroquine (HCQ)are commonly used for the treatment of Corona virus Disease 2019(COVID-19) in critically ill patients.It was hypothesized that HCQ as an aerosol application can reach the antiviral concentration of ~1–5 μM in the alveolar cells which has been proven effective in vitro. A physiologically-based pharmacokinetic (PBPK) model of nebulized HCQ for pulmonary delivery to COVID-19 patients using the Nasal-Pulmonary Module in GastroPlus® V9.7 simulator, in order to calculate the necessary inhalation dose regimen of HCQ, was developed. The physiological, drug disposition, and pharmacokinetic parameters were obtained from the literature and used during model building after optimization using Optimization Module, while oral data was used for validation. The 25 mg BID inhalation dosing was predicted to lead to alveolar HCQ levels of 7 µM (above EC50 of ~1–5 µM), and small plasma levels of 0.18 µM (as compared to plasma levels of 3.22 µM after 200 mg BID oral dosing). However, average contact time (>1 µM) is around 0.5 h in lung parts, suggesting indirect exposure response effect of HCQ.The developed PBPK model herein predicted HCQ levels in plasma and different lung parts of adults after multiple inhalation dosing regimens for 5 days. This in-silico work needs to be tested in vivo on healthy subjects and COVID-19 patients using 12.5 mg BID and 25 mg BID inhalation doses.
Keywords: hyrdoxychloroquine; PBPK; gastroplus; COVID-19; pulmonary